Analisis Penerapan 5S di Tempat Kerja: Pendekatan dari Perspektif Karyawan PT. PKC - Tobing, Doni Ronaldo Lumban; Pratama, Dewa; Fasa, Nadia (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
A warehouse is a place used to store and store goods owned by a company. There are many activities carried out in the warehouse, starting from the goods data collection process to the goods management process. PT. PKC  is not yet optimal and there are still several problems such as a poor management system and irregular spare parts delivery scheduling. Therefore, the 5S method is needed so that warehouse management can be better and more efficient. There is the  5S method (Seiri, Seiton, Seiso, Seiketsu & Shitsuke) which is a management approach to organizing, cleaning, and maintaining an efficient, orderly, and productive work environment. The results of evaluation of 5S implementation in PT warehouse. PKC The assessment of the implementation of Seiri is included in a good classification with a score of 62%, the assessment of the implementation of Seiton is also in a good classification with a score of 67%, the assessment for the implementation of Seiso, is classified as good with a score of 74%, while the assessment for Seiketsu is in a reasonable classification with a score of 50%, and the assessment for the implementation of Shitsuke is categorized as sufficient with a score of 50%. Keywords: Implementation, Warehouse, 5S Method